A non-contrastive cue in spontaneous imitation: Comparing mono- and bilingual imitators. (September 2021) - Kwon, Harim
Highlights: English and Seoul Korean speakers shadowed English voiceless stops. English speakers shadowed voiceless stops with different manipulations distinctively. Imitation induced by the contrastive cue retains in subsequent productions. Seoul Korean speakers do not draw on their native phonology in L2 imitation tasks. The role of phonology in spontaneous imitation is discussed. Abstract: This study tests the hypothesis that imitators of different native languages imitate the same targets in distinct ways predicted by their native phonology, by investigating the role of a non-contrastive phonetic property in spontaneous imitation of English voiceless stops by English monolingual and Seoul Korean-English bilingual imitators. The primarily contrastive phonetic property for English voiceless stops is voice onset time (VOT), with the fundamental frequency (f0) of the post-stop vowel being non-contrastive but still informative for the voicing contrast. On the other hand, in Seoul Korean, stop VOT is a non-primary cue, but it is necessary to maintain the full three-way laryngeal contrast in the language. Post-stop f0 is the primary cue for the Seoul Korean aspirated stops. Seoul Korean speakers have been reported to imitate aspirated stops with longer VOT by raising their post-stop f0 (Kwon, 2019 ). In this study, English monolingual speakers and Seoul Korean-English bilingual speakers heard and shadowed model speech containing English voiceless stops manipulated by either raising post-stop f0 or lengthening VOT. Their imitation was assessed with two acoustic measurements, stop VOT and post-onset f0, of the voiceless stops, before and after the imitators heard the model speech with the two manipulations. A separate discrimination test confirmed that both manipulations were reliably perceived by both the monolingual and the bilingual imitators. English monolingual speakers' imitation data suggest that their shadowing productions reflect the phonological significance of the two phonetic properties, and only the imitative changes induced by a contrastive cue last beyond the immediate shadowing targets. In addition, Seoul Korean-English bilingual speakers, when performing the spontaneous imitation tasks in English, do not draw on their native (Seoul Korean) phonology. Implications of these findings on the role of phonology in the spontaneous imitation of bilingual and monolingual speakers are discussed.